Validation of 4-meter-gait-speed test and 5-repetitions-sit-to-stand test in patients with pulmonary fibrosis: a clinimetric validation study - Bloem, Ada; Veltkamp, Marcel; Spruit, Martijn A.; Custers, Jan W.H.; Bakker, Eric W.P.; Dolk, Hanneke M.; Grutters, Jan C. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2018)
Background and objective: Patients with pulmonary fibrosis (PF) have a clear exercise intolerance. The 4-meter-gait-speed (4MGS) test and the 5-repetitions-sit-to-stand (5STS) test are easy, inexpensive and reliable measures of functional performance. Both tests have been validated in healthy adults and patients with chronic obstructive pulmonary disease. 4MGS test and 5STS test have not been studied in patients with PF. Methods: In this cross-sectional clinimetric validation study 51 PF patients conducted in random order the 4MGS test, 5STS test and the 6-min walk test (6MWT) on a single day. Additionally, body weight, height, lean body mass, health-related quality of life, disease severity, handgrip strength, dyspnoea and leg fatigue were assessed. The setting was a tertiary referral center for Interstitial Lung Diseases. Results: Patients had a diagnosis of idiopathic pulmonary fibrosis (IPF, 37%), PF other than IPF (47%), or unclassified (16%). Patients walked 453±111m in six minutes. Moreover, it took the patients 2.0±0.5s to walk 4 m, and 12.0±3.8s for the 5STS test. The 4MGS test (r = 0.77; p<0.01) and the 5STS test (r = -0.41; p<0.01) correlated significantly with the distance walked in 6MWT. Indeed, 4MGS combined with handgrip strength and Medical Research Council dyspnoea grade could explain 75% of the variance in 6MWD. Conclusions: 4-meter-gait-speed and 5-repetitions sit-to-stand are significantly and independently correlated with the 6-minute walk distance in patients with pulmonary fibrosis. Indeed, 4-meter-gait-speed test may serve as a simple initial field test to assess exercise performance in patients with pulmonary fibrosis.